Cloud connectivity and embedded sensory systems - Spaanenburg, Lambert; Spaanenburg, Hendrik (Springer, 2011)
This book sets out a new theory on the design of wireless sensor networks, based on concepts developed for large-scale, distributed computing environments known as 'cloud computing'. It includes design examples relevant to a range of applications